THE CONTRIBUTION OF THE INTERVENTION PLAN IN AN INDUCTION WORKSHOP FOR OBSERVANT DANCE TEACHERS TO INCREASING THE LEVELS OF PROFESSIONAL COMMITMENT AND SATISFACTION - USM ADMIN (Moldova State University, 2015)
The article examines the contribution of a model for an intervention plan of female observant dance teachers in their first year of teaching, to their coping with difficulties teaching and to an increase in their commitment to teaching and satisfaction therewith. The findings show that there was a significant decrease in the general index of the difficulties, the perception of satisfaction with teaching increased significantly between the beginning of the workshop and its conclusion, and a tendency of increasing was found in the perception of commitment to teaching. Keywords: satisfaction, commitment, intervention plan model, induction workshop, dance teachers.